Dynamic Footprints of the Specific Artificial Spin Ice Microstate on Its Spin Waves - Pietro Micaletti; Federico Montoncello (Magnetochemistry, 2023)
We present a micromagnetic investigation of the spin dynamics at remanence (zero applied field) in a periodic square artificial spin ice (ASI) prepared four different microstates (i.e., with zero, two or four magnetic charges at the vertex). The ASI elements consist of permalloy elliptical dots with a fixed long axis, and a variable width and interdot separation. For each vertex configuration, we compute the equilibrium ground state at zero applied field by relaxing a previously set magnetic configuration (microstate). After the excitation of such ground state, we perform a Fourier analysis obtaining frequency spectra and space phase profiles. We discuss the behavior of the spectra in changing the system’s microstate and geometry, with reference to the spin mode space profiles, magnetization configuration, and effective internal field. Our results draw a correlation between ASI macrospin orientation at vertex and a few important dynamic properties like a phase-shift in the mode profiles or the frequency gap between the edge and fundamental modes. We suggest a few specific experiments to validate of our predictions, as well as applications in the field of interferometric magnonic devices. We believe that our results can help, from the fabrication stage, in tailoring the appropriate ASI geometry for specific application purposes.